Programmes to support chronic disease self‐management: should we be concerned about the impact on spouses?. (27th February 2013) - Masters, Stacey; Oliver‐Baxter, Jodie; Barton, Christopher; Summers, Michael; Howard, Sara; Roeger, Leigh; Reed, Richard
Abstract Chronic disease self‐management support (CDSMS) programmes are widely advocated as an essential element of chronic disease care and have demonstrated increased engagement with self‐care activities such as improving diet but may place additional strain on spouses. This study used an embedded mixed methods approach to explore the impact of CDSMS on spouses. Spouses were recruited as part of a larger randomised controlled trial to assess the efficacy of a health professional‐led CDSMS programme (the Flinders Program) in older adults with multiple chronic conditions, compared with an attention control group. Spouses were recruited from the general community through General Practitioners located in the southern areas of Adelaide, Australia. Quantitative and qualitative data were collected between September 2009 and March 2011; a total of 25 spouses from each of the CDSMS and control groups provided data. Spousal strain was measured by the Caregiver Risk Screen (CRS). Few spouses had CRS scores indicative of moderate or high strain at baseline or upon completion of the study and CRS scores did not differ by programme allocation. Spouses of participants with poorer self‐management (r = 0.34, P = 0.016) and more illness intrusiveness (r = 0.35, P = 0.013) had higher CRS scores at baseline (quantitative) and spousal strain was found to increase as a partner's well‐being and capacity to self‐manage decreased (qualitative). Spouse presence at CDSMS sessions (20%) frequently signalled a reduced level of partner well‐being. Overall, our findings suggest that CDSMS programmes in many cases will have little impact (either positive or negative) on spousal strain. A significant increase in spousal strain may occur, however, if there is deterioration in the health status of a CDSMS participant. The impact of decline in participant health status on carer strain needs to be considered in CDSMS programmes.